Low Context Communication Foreign Students From Lospalos -Timor Leste In Organizasaun Lospalos Uan Ukani Bandung - Felisianus Efrem Jelahut; Siti Karlinah; Evi Novianti (International Journal of Communication and Society, 2021)
Organizasaun Lospalos Uan Ukani Bandung is an association of foreign students from Lospalos-Timor Leste studying in Bandung. Student members of this organization come from the city of Lospalos, Timor Leste. Their culture and language is fataluku which is a culture with high context communication. This study aims to determine the communication style of students who are members of the organization. The theoretical framework used in this research is Symbolic Interaction which examines the meaning that arises from the reciprocal interaction of individuals in the social environment with other individuals and focuses on the question of what symbols and meanings can arise from interactions between humans in a small to a wider scope. such as groups, organizations or social communities such as what happened in Organizasaun Lospalos Uan Ukani. The method used in this research is qualitative-descriptive. The results of the study prove that the communication style of students from the Los Palos uan Ukani Bandung organization is a low context communication style that is different from the fataluku culture communication style which is classified as a high context cultural communication style. This difference is caused by the mixing of the multilingual communication students of the Los Palos uan Ukani Bandung organization.